Internal versus External Growth in Industries with Scale Economies: A Computational Model of Optimal Merger Policy - Ben Mermelstein; Volker Nocke; Mark A. Satterthwaite; Michael D. Whinston (University of Mannheim, Department of Economics, 2014)
We study optimal merger policy in a dynamic model in which the presence of scale economies implies that firms can reduce costs through either internal investment in build- ing capital or through mergers. The model, which we solve computationally, allows firms to invest or propose mergers according to the relative profitability of these strategies. An antitrust authority is able to block mergers at some cost. We examine the optimal policy when the antitrust authority can commit to a policy rule and when it cannot commit, and consider both consumer value and aggregate value as possible objectives of the antitrust authority. We find that optimal policy can differ substantially from what would be best considering only welfare in the period the merger is proposed. We also find that the abil- ity to commit can lead to a significant welfare improvement. In general, antitrust policy can greatly affect firms' optimal investment behavior, and firms' investment behavior can in turn greatly affect the antitrust authority's optimal policy.
urn:nbn:de:bsz:180-madoc-359587
Keywords: L41; L13; 330; Merger Policy; Antitrust; Investment; Entry; Commitment